2006
DOI: 10.3102/00346543076004607
|View full text |Cite
|
Sign up to set email alerts
|

Challenges New Science Teachers Face

Abstract: Providing support focused on real challenges is critical in retaining highly qualified new science teachers, but the field lacks a systematic description of these teachers’ needs. The authors of this article examine the areas that science teachers are expected to understand: (1) the content and disciplines of science, (2) learners, (3) instruction, (4) learning environments, and (5) professionalism. They review the literature on challenges facing preservice and early-career science teachers, identify issues on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
319
1
8

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 418 publications
(348 citation statements)
references
References 177 publications
11
319
1
8
Order By: Relevance
“…To identify a research-base for characterizing these challenges, we reviewed the literature on beginning science teachers (Davis, Petish, & Smithey, 2006). We summarize some findings of our review, as related to beginning elementary teachers of science, to position the importance of our goals.…”
Section: Overcoming Challenges Through Addressing Goalsmentioning
confidence: 99%
“…To identify a research-base for characterizing these challenges, we reviewed the literature on beginning science teachers (Davis, Petish, & Smithey, 2006). We summarize some findings of our review, as related to beginning elementary teachers of science, to position the importance of our goals.…”
Section: Overcoming Challenges Through Addressing Goalsmentioning
confidence: 99%
“…In particular, research has suggested the importance of ensuring that science teachers can fluently discern which instructional resources to use to target specific learning goals, to provide insight into student thinking, and to address specific student challenges (Carlsen, 1991;Schneider & Plasman, 2011). One of the most important aspects of this practice for a science teacher is being able to use one's subject matter knowledge to determine whether and how specific instructional strategies and resources can be employed to engage students productively with scientific phenomena, although this can be challenging, especially for novice teachers (Carlsen, 1991;Davis, Petish, & Smithey, 2006;Schneider & Plasman, 2011). It is important that science teachers understand the different ways in which scientific phenomena can be represented, for example, through a wide array of models, examples, or simulations, and be able to use these various representations to challenge student ideas (Clermont, Borko, & Krajcik, 1994;Schwarz et al, 2009).…”
Section: Conceptualizing Practice-based Measures Of Content Knowledgementioning
confidence: 99%
“…Beginning teachers need to learn how to address problems of practice such as engaging students in science, organizing instruction and developing productive learning communities-and in doing so, develop their knowledge, teaching practices, and dispositions. Preservice teachers recognize these problems of practice as important, though from a somewhat different perspective (Abell, Bryan, & Anderson, 1998;Davis et al, 2006;Howes, 2002;Schwarz et al, 2008). They want to engage their own students in interesting and real-world science information, teach science in a manner that is more fun, exciting and relevant than it frequently was for them as former students, and fix science misconceptions.…”
Section: Introductionmentioning
confidence: 99%
“…Preservice and beginning teachers face a number of challenges in learning how to teach science effectively (Appleton, 2006;Davis, Petish, & Smithey, 2006). These challenges include developing their professional knowledge about science content, scientific practices and discourses, and the nature of science (National Research Council [NRC], 2007) as well as their knowledge about learners' strengths, needs, and ways of knowing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation